Design process of low cost uncemented femoral stem 316L stainless steel using investment casting technique - Baharuddin, Mohd Yusof; Salleh, Sh-Hussain; Mohd Noor, Alias; Lee, Muhammad Hisyam; Zulkifly, Ahmad Hafiz; Omar, Mohd Afian (Trans Tech Publications, Switzerland, 2016)
Total hip replacement (THR) is a flourishing orthopaedic surgery which is generating billion of dollars of revenue. The cost associated with the fabrication of implants has been increasing year by year and this phenomenon has burdened the patient with extra charges. Consequently, this study will focus on designing an accurate implant via implementing the reverse engineering of three dimensional morphological study based on a particular population. By using the finite element analysis, this study will assist to predict the outcome and could become a useful tool for pre-clinical testing of newly designed implant. A prototype is then fabricated using 316L stainless steel by applying investment casting techniques which reduce manufacturing cost without jeopardizing the implant’s quality. The finite element analysis showed the maximum von Mises stress was 66.88 MPa proximally with a safety factor of 2.39 against endosteal fracture, and micromotion was 4.73 μm which promotes osseointegration. This method offers a fabrication process of cementless femoral stems with lower cost, subsequently helping patients, particularly those from non-developed countries.